The division into chapters and their titling in the "Dialogues" of Gregory the Great - Galán Sánchez, Pedro Juan (Cuadernos de Filología Clásica. Estudios Latinos, 2012)
The aim of this paper is to demonstrate that the division into chapters and their titling in the Dialogues of Gregory the Great are not ascribable to the work’s author, but both structuring elements of the text were introduced by a later copyist. Two types of proof are provided in order to confirm this: firstly, some arguments based on external data provided by the handwritten tradition and the critical editions; secondly, some arguments based on internal data which appear in the analysis (on the form and on the content) of the work itself.